Enhancing Spinach (Spinacia oleracea L.) Growth and Soil Health Using Biochar-Coated Potassium Fertilizer - Masood Ahmed khan; Muhammad Adnan Karim; Salma Malik; Muneeba Arooj; Waseem Ahmed; Asif Ali Mastoi; Muhammad Asif Khan, (Dialogue Social Science Review (DSSR), 2025)
This study was carried out in the wirehouse of the College of Agriculture, University of Sargodha, using potted plants to test how biochar-coated potassium fertilizer (BC-K) affects spinach (Spinacia oleracea L.) growth in cadmium (Cd)-contaminated soil. The goal was to improve soil health, reduce Cd availability, and increase spinach yield. The experiment followed a completely randomized design (CRD) with eight treatments and three replications, making a total of 24 pots. The treatments included a control (no fertilizer), recommended NPK, biochar alone, different doses of BC-K (1.5, 2.0, and 2.5 g per pot), and BC-K combined with micronutrients (Zn, Fe, B, Mn, Cu) and full fertilizer application. Results showed that BC-K improved soil fertility by increasing organic matter, making nutrients more available, and reducing Cd toxicity. Spinach plants treated with BC-K and full fertilizer had the best growth, with taller plants, more leaves, and higher fresh and dry weight. BC-K application also lowered Cd levels in spinach leaves, making it a safer food choice. This study suggests that biochar-coated potassium fertilizer is a useful and eco-friendly way to grow spinach in polluted soils. It helps increase crop yield, improves soil quality, and enhances food safety, making it a good option for sustainable farming.